The RNA landscape of Dunaliella salina in response to short-term salt stress - Zhang, Bingbing; Deng, Caiyun; Wang, Shuo; Deng, Qianyi; Chu, Yongfan; Bai, Ziwei; Huang, Axiu; Zhang, Qinglian; He, Qinghua (Frontiers in Plant Science, 2023)
Using the halotolerant green microalgae Dunaliella salina as a model organism has special merits, such as a wide range of salt tolerance, unicellular organism, and simple life cycle and growth conditions. These unique characteristics make it suitable for salt stress study. In order to provide an overview of the response of Dunaliella salina to salt stress and hopefully to reveal evolutionarily conserved mechanisms of photosynthetic organisms in response to salt stress, the transcriptomes and the genome of the algae were sequenced by the second and the third-generation sequencing technologies, then the transcriptomes under salt stress were compared to the transcriptomes under non-salt stress with the newly sequenced genome as the reference genome. The major cellular biological processes that being regulated in response to salt stress, include transcription, protein synthesis, protein degradation, protein folding, protein modification, protein transport, cellular component organization, cell redox homeostasis, DNA repair, glycerol synthesis, energy metabolism, lipid metabolism, and ion homeostasis. This study gives a comprehensive overview of how Dunaliella salina responses to salt stress at transcriptomic level, especially characterized by the nearly ubiquitous up-regulation of the genes involving in protein folding, DNA repair, and cell redox homeostasis, which may confer the algae important mechanisms to survive under salt stress. The three fundamental biological processes, which face huge challenges under salt stress, are ignored by most scientists and are worth further deep study to provide useful information for breeding economic important plants competent in tolerating salt stress, other than only depending on the commonly acknowledged osmotic balance and ion homeostasis.